Patterns in the development of collective immunity to SARS-CoV-2 during the COVID-19 pandemic - A. Yu. Popova; V. S. Smirnov; S. A. Egorova; I. V. Drozd; A. M. Milichkina; A. M. Dashkevich; Z. S. Nurmatov; G. G. Melik-Andreasyan; M. M. Ruziev; Areg A. Totolian (Медицинская иммунология, 2023)
The ongoing coronavirus disease (COVID-19) pandemic over the past three years has caused close attention to the problem of herd immunity, which is understood as: "resistance to the spread of a contagious disease within a population or herd". Collective immunity is formed both as a result of infection (natural spread of the pathogen in a population of susceptible individuals) and as a result of the use of specific vaccines. During the COVID-19 pandemic, both mechanisms for the formation of collective immunity were realized. In the first wave, there was a natural formation of collective immunity to the virus following recoveries from COVID-19 caused by pandemic spread of SARS-CoV-2. Starting from December 2020, the widespread use of specific vaccines against SARS-CoV-2 began in the USA, Great Britain, China, Russia, and a number of other countries. This launched the process of post-vaccination collective immunity formation; its features have depended on the vaccine types implemented. Currently, in those countries where vaccination and revaccination of recovered patients is widely carried out, immunity is "hybrid" in nature. Several commonalities should be noted in the pandemic experience: a somewhat regular, periodic (wavelike) nature of the COVID-19 epidemic process; changes in pathogen genetics in variants in all countries; and expansive mass vaccination programs in many populations. From these, we can draw some conclusions about the general trend for all countries in the formation of collective immunity during the pandemic: At the beginning of the pandemic in 2020, overall population seroprevalence did not exceed 20%. Other findings were: the highest seroprevalence rates were noted in the children's age group; pronounced regional differences were revealed; and the highest indicators were noted among medical workers. Collective immunity developed as a result of infection or illness, and in the majority of seropositive volunteers, it was represented by antibodies to both antigens. At the height of the pandemic in the summer of 2021, population seroprevalence reached 50%. This was due to both a significant number of convalescents and the start of mass vaccination campaigns. In all countries, specific differences in seroprevalence (by age, region, profession) leveled out, leading to more uniformity. During this period, the formation of "hybrid" immunity is clearly prominent, and the proportion of individuals with antibodies to RBD alone increased (due to vaccination with vector vaccines).  Later, mass vaccination, as well as involvement of most of the population in the epidemic process due to the emergence of the highly contagious Omicron strain, raised the level of collective immunity to 80-90%. This led to a sharp decrease in COVID-19 incidence in the second half of 2022 in all countries participating in the study. In the later stages of the pandemic (2022-2023), almost 90% of seropositive volunteers had hybrid immunity, reflected as antibodies to both antigens (Nc, RBD).